Effects of Occupational Exposure on Health of The Workers of Copper Manufacturing Utensils in Kashmir (India) - Khursheed Wani; Kounsar Jan; Abu Waleed Shah (ILUNI MKK FKUI and PRODI MKK FKUI, 2023)
Purpose: The objective was to investigate the general working conditions of the workers of copper manufacturing Utensils in Kashmir (India) and to assess the health risk factors of the workers working in that industry.Methods: The study was conducted at 30 workshops manufacturing copper utensils of Kashmir valley situated in India. Temperature, Noise level was also measured in these units by following standard protocols. A formulated questionnaire was circulated among the workers to assess the health risk factors of the workers and observation method was utilized to evaluate the working conditions of theses workshops Results: The present investigation indicates that the majority of the workers of these factories industry were illiterate. Most of them were suffering from health problems like eye irritation, injuries, back pain, skin injuries, respiratory problems and general weakness.Conclusions: Our results clearly indicated that the health and working conditions of the workers manufacturing copper utensils in Kashmir (India) were unsatisfactory. Every worker on an average was suffering from three to five health-risk factors. We recommend that personal protective equipments should be provided to the workers to reduce the risk factors. : The objective was to investigate the general working conditions of the workers of copper manufacturing Utensils in Kashmir (India) and to assess the health risk factors of the workers working in that industry.